Dihydroxyacetone: A safe camouflaging option in vitiligo - Natta Rajatanavin (2018)
Background: Most treatment protocols for vitiligo usually do not result in complete repigmentation. Therefore, cosmetically acceptable camouflage, low cost and easy to handle alternatives are warranted. Objective: To evaluate the efficacy of low-cost self-tanner available in the Thai market in normal subjects with skin types III, IV, and V, and the efficacy for camouflage of 6% dihydroxyacetone (DHA) cream in the treatment of vitiligo on exposed areas of Asian skin. Methods: The study was divided into two parts. Part 1 is a prospective study of 15 healthy volunteers using three different DHA creams which were available in the Thai market with concentrations of 3.5%, 4.2%, and 5%. Part 2 was a retrospective study of 20 patients suffering from vitiligo affecting the face and/or hands and feet who were treated with 6% DHA. The data were collected through direct examination, telephone interview, face-to-face interview, and photographs. Results: In healthy volunteers, we found that color matching was achieved by using a higher concentration of DHA in darker-skin subjects. Most of the vitiligo patients (88.9%) reported moderate to marked satisfaction with the cosmetic results of 6% DHA cream. Conclusion: Dihydroxyacetone offers a safe and effective therapeutic option for recalcitrant vitiligo. Dark-skin subjects need a higher concentration of DHA cream than lighter-skin subjects. © 2008 The International Society of Dermatology.